Methods for measuring the spatial mobility of tourists using a network theory approach - Nod, Gabriella; Aubert, Antal (Hungarian Geographical Bulletin, 2022)
The present study uses the methodological tools of network theory to investigate the spatial movements of tourists in the sample area, which is the South Transdanubian tourism region of Hungary. The basic idea of the study is that tourist movements across settlements in a larger tourist destination make a coherent network. As long as the approach is correct, this network can be measured by properties that are characteristic of networks, such as centrality or degree. A review of the methodology of similar studies previously published on the subject has been used to supplement the method of analysis used below. As a result, the study not only characterised the sample area municipalities in terms of network characteristics, but also classified them into clusters for strategic planning purposes on the basis of the mobility propensity of the tourists staying there.